2004
DOI: 10.1007/s11249-004-8083-z
|View full text |Cite
|
Sign up to set email alerts
|

A New Low Friction Concept for High Temperatures: Lubricious Oxide Formation on Sputtered VN Coatings

Abstract: The binary system of vanadium and nitrogen offers promising phases in order to enhance the tribological properties of common hard coatings, owing to their ability to form lubricious oxides, often also referred to as Magne´li phases, at elevated temperatures. The aim of this work is to characterize VN coatings prepared by reactive unbalanced magnetron sputtering, and to verify the new concept of solid/liquid oxide lubrication. Oxidation of the coatings and possible melting of the oxides were investigated by dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(53 citation statements)
references
References 24 publications
6
46
0
1
Order By: Relevance
“…This is consistent with the static oxidation studies that showed the V2O5 dominant outer surface on top of AlVO4 and TiO2 particles [10]. The present observations are also consistent with the findings of Gassner et al [7] and Fateh et al [8], who observed VO2 and possibly V6O13 as well as V2O5. In any event, it is clear that, as expected, the low friction is promoted by the outer V2O5 layer, which provides some mechanical support as a result of the compacted nanocrystalline nature (often referred to as a glaze layer).…”
Section: Friction Behaviour At 635 0 Csupporting
confidence: 94%
See 1 more Smart Citation
“…This is consistent with the static oxidation studies that showed the V2O5 dominant outer surface on top of AlVO4 and TiO2 particles [10]. The present observations are also consistent with the findings of Gassner et al [7] and Fateh et al [8], who observed VO2 and possibly V6O13 as well as V2O5. In any event, it is clear that, as expected, the low friction is promoted by the outer V2O5 layer, which provides some mechanical support as a result of the compacted nanocrystalline nature (often referred to as a glaze layer).…”
Section: Friction Behaviour At 635 0 Csupporting
confidence: 94%
“…Similarly, wear tests of Ti-Al-V-N monolithic films (2.40 at.% ≤ V ≤ 11.10 at.%) against an Al2O3 ball exhibited friction coefficients in the range of 0.6-0.85 at 25 0 C, which increased to 1.1 at 500 0 C and dropped to the range of 0.8-0.2 at 700 0 C (friction coefficient value depended on the concentration of V) [6]. Wear studies of VN coatings by Gassner et al [7] and Fateh et al [8] confirmed the reduced friction coefficient associated with the formation of lubricious vanadium oxides, i.e. Magne´li phases at elevated temperatures.…”
Section: Introductionmentioning
confidence: 97%
“…Due to the lower shear strength of V2O5 oxide than other oxides, the V-O containing tribofilm exhibited lower friction coefficient. Similar low friction has been found in binary VN coatings [37] where TiAlN, another constituent subphase in the TiAlN/VN, generally exhibits high friction [13,14]. The extremely low wear coefficient of TiAlN/VN can be explained in three aspects.…”
Section: Discussionsupporting
confidence: 65%
“…V 2 O 5 , Ag 2 Mo 2 O 7 ) [6][7][8][9]. Among these elements, particular attention has been given to the vanadium-containing coatings (Magnéli phases V n O 2n−1 ), which showed interesting tribological properties in the temperature range 500-700•C [2,[10][11][12][13][14][15]. Dissimilar series of V-based hard coatings have been developed, such as ternary…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Note that Ti 0.80 Si 0.15 N film was tested at higher temperature than V rich coating since no signals of oxidation were detected at lower temperature. On the other hand, the oxidation resistance of the V rich coating could not be studied at 900 ºC due to melting of V 2 O 5 (~685 ºC) [7,13,24] and consequent degradation of the film [26]. respectively.…”
Section: Characterization Of the As-deposited And Oxidized Coatingsmentioning
confidence: 99%